STREET NAME APPLICATION PROGRAM SEARCH ON JAKARTA MAP USING VISUAL BASIC 6.0 - John Hery Setiawan; Eko Hadiyanto, SSi, MM (Jurnal Sistem Informasi, 2002)
Writing is about the search application program name of the street on the map. So it was expected that these programs can provide a fast and efficient and useful for the public to be more practical in providing reliable information.Â  In the course of this map jakarta authors explain the steps making a simple program to use Visual Basic 6.0 Program is carried out mainly focuses on the appearance of the map drawing and design programs that attract or according to your imagination. Â With a map program is expected to search a street name on the map will be easier and faster, in preparing the picture is very clear.